The Role of Forests in Low Carbon Transition: A Systematic Literature Review - Stanislovaityte, Gabija; Jankovic, Marija; Mikalauskiene, Asta; Ciegis, Remigijus; Lauzadyte-Tutliene, Agne (Transformations In Business & Economics, 2025)
The use of a carbon sink mechanism plays an important role in achieving a low-carbon transition. Forest-based carbon sequestration assumes a notable role in the suite of ecosystem services that influence global climate dynamics. The paper aims to conduct a systematic literature review on the role of forests in decarbonising the economy, define the research gap, and develop a future research agenda. The SALSA and PRISMA frameworks and the PSALSAR protocol were used in the systematic literature review. The main findings of the analysis showed that there is a lack of integrated studies addressing the water, land, climate, energy, agriculture, and forests nexus for defining the harmonised climate change mitigation policies targeting specific sectors of the economy linked to natural resources, as decarbonisation can be achieved through various climate change mitigation and carbon sequestration measures in interlinked water-land-climate-food-energy-forests systems.